2021
DOI: 10.1186/s12879-021-06567-w
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in people living with HIV in Romania and Spain

Abstract: Background Health-related quality of life (HRQoL) is a crucial component in assessing and addressing the unmet needs of people, especially those with chronic illnesses such as HIV. The aim of the study was to examine and compare the health-related quality of life of people living with HIV in Romania and Spain, compared to the general populations of each country. Methods A cross-sectional survey was conducted among adults (≥ 18 years) attending for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…Previous studies have reported that HIV infection-related health impairments, including opportunistic infections, tumors, and malnutrition will not only reduce the quality of life of PLWHA but are also be affected by factors such as sex, age, economic status, marital status, educational level, CD4 + T cell count, and viral load ( 19 21 ). Available evidence reveals that anemia is quite common in PLWHA and is significantly associated with an increased risk of premature death ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that HIV infection-related health impairments, including opportunistic infections, tumors, and malnutrition will not only reduce the quality of life of PLWHA but are also be affected by factors such as sex, age, economic status, marital status, educational level, CD4 + T cell count, and viral load ( 19 21 ). Available evidence reveals that anemia is quite common in PLWHA and is significantly associated with an increased risk of premature death ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The success of antiretroviral therapy (ART) has lessened the clinical complications of HIV infection and increased the survival rate of PLWH, with the infection now considered a chronic disease in those countries where treatment is accessible [ 4 , 5 ]. Nevertheless, previous research indicated that PLWH have a worse health-related quality of life (HRQoL) than the general population [ 6 , 7 , 8 ]. Most of these studies considered HRQoL to be a multidimensional construct comprising factors such as physical, emotional, cognitive, and social functioning [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, previous research indicated that PLWH have a worse health-related quality of life (HRQoL) than the general population [ 6 , 7 , 8 ]. Most of these studies considered HRQoL to be a multidimensional construct comprising factors such as physical, emotional, cognitive, and social functioning [ 6 , 7 ]. Using validated instruments, they found worse HRQoL in PLWH in all the domains, particularly anxiety and depression, but also poor self-rated health status, than in people without HIV [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations